The founder of the Hare Krishnas as seen by devotees : a cognitive study of religious charisma - Ketola, Kimmo (Studies in the history of religions, 2008)
The Hare Krishna movement is one of the most well-known new religious movements in the Western societies. It was founded in New York in 1966 by the Indian monk A.C. Bhaktivedanta Swami Prabhupda (1896-1977).